The alkalinity generation potential of olivine and oyster shell for laboratory experiments: testing the effects of ocean alkalinity enhancement - Cale A Miller; Fabrice Pernet (Environmental Research Communications, 2025)
Ocean alkalinity enhancement has emerged as a predominant line of marine carbon dioxide removal research. Of paramount importance associated to OAE application is the need to understand the biological impacts. Within this context, we present a framework for generating alkaline solutions, based on an alkalinity generation potential from the dissolution of olivine (Mg-silicate) and biogenic calcium carbonate (CaCO _3 ) in seawater that can be used for conducting biological experiments. Using established dissolution rates for both minerals as a scaling factor, we show that olivine dissolution can generate enriched seawater solutions of 9000 μmol kg ^−1 above background alkalinity when dissolving at a pH between 5.5–6.5. Similarly, CaCO _3 dissolution from crushed oyster shell reached ∼10000 μmol kg ^−1 at a calcite saturation state of < 0.1. Further, we assessed the sensitivities of carbonate chemistry dissociation constants and the calcium carbonate solubility on subsequent enrichment of Mg ^2+ and Ca ^2+ from mineral dissolution. This was done by modifying the calculations in CO2SYS (Matlab v3). The results showed that increased [Ca ^2+ ] raises pH by 0.4 units above non-enriched seawater, while enriched [Mg ^2+ ] lowers p CO _2 values by 20 μatm. Thus, we demonstrate how to produce necessary experimental conditions for a wide range of applications when testing biological sensitivities to OAE while accounting for the modifications to the carbonate system.